Investigation into the potential mechanism and molecular targets of Fufang Xueshuantong capsule for the treatment of ischemic stroke based on network pharmacology and molecular docking - Wang, Lei; Wang, Liping; Wang, Hui; Zhu, Ting (Frontiers in Pharmacology, 2022)
Fufang Xueshuantong Capsule (FFXST) is a traditional Chinese medicine (TCM) preparation used to activate blood circulation, resolve stasis, benefit qi and nourish yin in clinical practice. However, its potential mechanism and molecular targets after ischemic stroke (IS) have not been investigated. The aim of this research was to investigate the molecular mechanisms of FFXST in the treatment of IS based on network pharmacology and molecular docking. We used the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) to collect candidate compounds of 4 herbs in FFXST; disease-related differential genes were screened using Gene Expression Omnibus (GEO) database and compound-disease network was created using Cytoscape 3.8.2 software. The topological analysis of the protein-protein interaction (PPI) network was then created to determine the candidate targets of FFXST against IS. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were conducted using the clusterProfiler package in R. The gene-pathway network of FFXST against IS was created to obtain the key target genes. Molecular docking was used to validate the core targets using AutoDock Vina 1.1.2. 455 candidate compounds of FFXST and 18544 disease-related differential genes were screened. Among them, FFXST targets for IS treatment has 67 active compounds and 10 targets in the PPI network having STAT1, STAT3 and HIF1A, etc. The biological processes of GO analysis included in regulation of reactive oxygen species metabolic process, cellular response to chemical stress, regulation of angiogenesis, regulation of vasculature development, positive regulation of cytokine production, and response to oxidative stress. The KEGG enrichment analysis including Kaposi sarcoma-associated herpesvirus infection, MicroRNAs in cancer signaling pathway, Th17 cell differentiation, and HIF-1 signaling pathway were significantly enriched. The network pharmacology outcomes were further verified by molecular docking. We demonstrated that FFXST protects against IS may relate to regulation of oxidative stress, immune inflammatory response, and angiogenesis through the relevant signaling pathways. Our study systematically illustrated the application of network pharmacology and molecular docking in evaluating characteristics of multi-component, multi-target, and multi-pathway of FFXST for IS.